Efek Cyclea Barbata Miers terhadap Viskositas Polimer Xanthan Gum untuk Reservoir 70°C - Rozi Afdi; Muhammad Rifqi Dwi Septian; Mohamad Obby Adianto (Mataram University, 2026)
One method to further enhance oil production is through tertiary recovery, also known as Enhanced oil recovery (EOR). The EOR method can increase production from wells by up to 75% recovery. One of the EOR technologies that has been applied for more than 50 years in the petroleum industry is polymer injection, which has proven effective in improving oil recovery. The objective of this study is to obtain an efficient polymer with good compatibility and viscosity. This research analyzes the compatibility and viscosity characteristics of Xanthan Gum (XG) polymer solutions and a mixture of Xanthan Gum with Cyclea barbata Miers (CHXG) in formation water with a salinity of 11,000 mg/L. Compatibility tests were conducted at concentrations of 1,000, 2,000, and 3,000 mg/L to determine the solubility of the polymer in formation water. The results show that both types of polymers have good compatibility, indicated by the absence of precipitation and the formation of clear and homogeneous solutions. Viscosity tests were carried out at room temperature and at elevated temperature (70°C) to evaluate the effect of temperature on the rheological properties of the solutions. The XG polymer exhibited a decrease in viscosity at 70°C, with the highest reduction of 24.3% at a concentration of 3,000 mg/L. In contrast, the CHXG polymer showed a significant increase in viscosity at high temperature, with the highest increase reaching 53.49% at the same concentration. These results indicate that the addition of Cyclea barbata Miers can enhance the thermal stability and viscosity performance of the polymer under reservoir conditions at 70°C, whereas the use of Xanthan Gum alone results in a decrease in viscosity at the same temperature.